Life Skills as an Element of Media for Learning Entrepreneurship for AUD Educators: Life Skills as an Element of Media for Learning Entrepreneurship for AUD Educators - Fitri Syahrida, Annisa; baiti, noor; Fatah, Abdul (Tawazuna, 2022)
The application of life skill education in suor educational institutions will give birth to outputs that have high competence, with us having the provision of life skills will be more productive and able to compete. which we often refer to as life skills.Library study is a method of data collection that is directed to the search for data and information through documents, both written documents, photographs, images, and electronic documents that can support the writing process." The results of the research will also be more credible if they are supported by existing photographs or academic and artistic papers." (Sugiyono, 2005:83).